Neurological and humoral control of blood pressure - O'Donohoe, P; Pandit, J (Elsevier, 2016)
There is a relationship between arterial blood pressure, cardiac output and vascular resistance which can be described mathematically, and helps us to understand the short-term control of blood pressure in the terms of a hydraulic system. The sensors in this system are the arterial baroreceptors which mediate changes in the hydraulic system through control of the autonomic nervous system, which in turn influences heart rate, inotropy and vascular tone. Altering the distribution of blood between the arterial and venous systems compensates for acute changes in total blood volume. The total blood volume is controlled predominantly by the kidney, with the renin-angiotensin-aldosterone system acting as both the 'sensor' of blood pressure/volume (via renin release in the juxtaglomerular apparatus) and the 'effector' of blood pressure/volume (via aldosterone secretion by the adrenal cortex). Overall control is shared; the baroreceptors being responsible for mediating short-term changes, and renal mechanisms determining the long-term control of blood pressure. These systems have to be adaptable in order to deal with physiological variation in the delivery of blood to tissues from rest to exercise, and with the large shifts in blood volume seen in acute haemorrhage. Pathophysiological changes in these systems lead to maladaptive responses, with systemic hypertension the most commonly seen.